2018
DOI: 10.31557/apjcp.2018.19.11.3225
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Insertion/Deletion Polymorphism is Associated with Breast Cancer Risk: A Meta-Analysis

Abstract: Background:A number of case-control studies were conducted to investigate the association of angiotensin converting enzyme insertion/deletion (ACE I/D) polymorphism with breast cancer. But the results remain controversial. This meta-analysis aims to comprehensively evaluate the association of ACE I/D polymorphism with breast cancer.Method:A comprehensive literature search on PubMed, Google Scholar, SCOPUS and ISI Web of Knowledge databases for studies published up to June 01, 2018 was performed. Summary odds r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Therefore, the assessment of heterogeneity is necessary, as high heterogeneity could be caused by the fact that there are actually two or more subgroups of studies present in the data, which have a different true effect. According to our previous metaanalyses, we suggested that heterogeneity might be due to differences in study design, sample size, genotyping methods, disease heterogeneity, and to the different roles played by gene-gene and gene-environment interactions (Aflatoonian et al, 2019a;Mirjalili et al, 2018;Moghimi et al, 2019Moghimi et al, , 2018. Moreover, after subgroup an analysis, heterogeneity was obviously decreased in Asians; however, the corresponding pooled ORs were not materially altered after deleting these studies, indicating that our results were statistically robust.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, the assessment of heterogeneity is necessary, as high heterogeneity could be caused by the fact that there are actually two or more subgroups of studies present in the data, which have a different true effect. According to our previous metaanalyses, we suggested that heterogeneity might be due to differences in study design, sample size, genotyping methods, disease heterogeneity, and to the different roles played by gene-gene and gene-environment interactions (Aflatoonian et al, 2019a;Mirjalili et al, 2018;Moghimi et al, 2019Moghimi et al, , 2018. Moreover, after subgroup an analysis, heterogeneity was obviously decreased in Asians; however, the corresponding pooled ORs were not materially altered after deleting these studies, indicating that our results were statistically robust.…”
Section: Discussionsupporting
confidence: 51%
“…A more recent metanalysis analyzing multiple study found no association of I/D polymorphism and PCa risk overall and among the Caucasian males in particular although the study found the D allele and the DD genotype associated with increased risk of PCa among the Asian and Latino males [28]. Similar inconsistencies were observed when the association of the I/D polymorphism and other cancers such as breast cancer [29,30], lung cancer [31,32], and colorectal cancer [33,34] was investigated.…”
Section: Discussionmentioning
confidence: 88%
“…However, CRC and GC have a complex etiology and pathophysiology generated by the interaction of several genes and environmental factors (7,42). Thus, besides the indeterminate number of characteristics that vary among studies, other confounding factors such as age, gender, lifestyle further contribute to between-study heterogeneity (43,44). In addition, there was a publication bias across the selected studies in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%